Tailoring the exchange interaction in covalently linked basic carboxylate clusters through bridging ligand selection - Alborés, Pablo (2012)
We are reporting new dimeric units of basic carboxylates bearing the Fe III 2M IIO motif for M = Co and Ni, covalently bound through the tetradentate bridging (LL) 2,2′-azopyiridine (azpy) and 2,3-di(2-pyridyl)quinoxaline ligands (dpq). We structurally characterized the hexanuclear clusters, and their magnetic properties have been fully analyzed. DFT calculations have been performed as a supplementary tool. All results evidence a weak antiferromagnetic interaction through the bridging ligands between isolated spin ground states arising from intra-Fe 2MO core exchange couplings. Together with the pioneer 2,2′-bipyrimidine bridged systems, the new complexes reported constitute a family of complexes where the exchange interaction can be tuned by the selection of the bridging LL type ligand. © 2012 American Chemical Society.